Hydrogen ventilation combined with mild hypothermia improves short-term neurological outcomes in a 5-day neonatal hypoxia-ischaemia piglet model. Issue 1 (December 2019) - Htun, Yinmon; Nakamura, Shinji; Nakao, Yasuhiro; Mitsuie, Tsutomu; Nakamura, Makoto; Yamato, Satoshi; Jinnai, Wataru; Koyano, Kosuke; Ohta, Kenichi; Morimoto, Aya; Wakabayashi, Takayuki; Sugino, Masashiro; et al.
Abstract Despite its poor outcomes, therapeutic hypothermia (TH) is the current standard treatment for neonatal hypoxic-ischaemic encephalopathy (HIE). In this study, due to its antioxidant, anti-inflammatory, and antiapoptotic properties, the effectiveness of molecular hydrogen (H2 ) combined with TH was evaluated by means of neurological and histological assessments. Piglets were divided into three groups: hypoxic-ischaemic insult with normothermia (NT), insult with hypothermia (TH, 33.5 ± 0.5 °C), and insult with hypothermia with H2 ventilation (TH-H2, 2.1–2.7%). H2 ventilation and TH were administered for 24 h. After ventilator weaning, neurological assessment was performed every 6 h for 5 days. On day 5, the brains of the piglets were harvested for histopathological analysis. Regarding the neurological score, the piglets in the TH-H2 group consistently had the highest score from day 2 to 5 and showed a significantly higher neurological score from day 3 compared with the NT group. Most piglets in the TH-H2 group could walk at day 3 of recovery, whereas walking ability was delayed in the two other groups. The histological results revealed that TH-H2 tended to improve the status of cortical gray matter and subcortical white matter, with a considerable reduction in cell death. In this study, the combination of TH and H2 improved short-term neurological outcomes in neonatal hypoxic-ischaemic piglets.